HUBUNGAN ANTENATALCARE DENGAN STUNTING PADA ANAK USIA 24-59 BULAN DI WILAYAH KERJA PUSKESMAS GEDANGSARI II KABUPATEN GUNUNGKIDUL - RR Viantika Kusumasari; Fitri Dian Kurniati; Dian Nur Adkhana Sari (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Relationship between Antenatal care and Stunting in Children aged 24-59 Months in the Working Area ofGedangsari II Health Center, Gunungkidul RegencyBackground: Gunungkidul has the highest rate of stunting among other DIY districts. Children/under five with stunting are likely suffering from reduced brain growth and cognitive function. Antenatal care/ANC is one among other factors causing stunting. Routine ANC visitearly pregnancy risks associated with nutritional problems. Objectives: :  This study aims to find the relationship between ANC and stunting on children aged 24-59 months in Puskesmas Gedangsari II Gunungkidul. Methods: This study was analytical survey research using case control approach. The sample in this study were mothers and their children aged 24-59 months who belong to inclusive and exclusive criteria. The sample were selected using purposive sampling, resulting in 22 respondents for case group and 22 respondents for control group. The instruments used in this study were microtoise and KIA book. The data for this study was analyzed using chi square.  Results: The chi square testing showed that p-value = 0.09, meaning that there is no relationship between ANC and stunting. Conclusion: There is no relationship between ANC and stunting on children aged 24-59 months in Puskesmas Gedangsari II Gunungkidul.